2023
DOI: 10.1177/21582440231199692
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Language Proficiency Scales in Education Context: A Systematic Literature Review

Aihua Zhu,
Samah Ali Mohsen Mofreh,
Sultan Salem

Abstract: The application of the language proficiency scales (LPS) in education validates its function, as it can explore the value in-depth. However, little systematic research on applying LPS has been conducted due to the complex intertwining of stakeholders and a lack of theoretical framework and practical approaches. Adopting the framework proposed by Y. Jin and Jie (2020), this study explored how the Common European Framework of Reference (CEFR) and China’s Standards of English (CSE) were used and impacted various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…In addition to the comparison on the target audience and language, the third comparison between the CEFR and CSE is their application in education. Zhu et al (2023) used the systematic literature review as the method to explore the application of CEFR and CSE. It was found that the CEFR and CSE were used in education by researchers, teachers, and test makers.…”
Section: The Application Of Cefr and Cse In Educationmentioning
confidence: 99%
“…In addition to the comparison on the target audience and language, the third comparison between the CEFR and CSE is their application in education. Zhu et al (2023) used the systematic literature review as the method to explore the application of CEFR and CSE. It was found that the CEFR and CSE were used in education by researchers, teachers, and test makers.…”
Section: The Application Of Cefr and Cse In Educationmentioning
confidence: 99%